THE EFFECT OF REIKI THERAPY ON POSTTRAUMATIC GROWTH (PTG) AMONG CHRONIC RENAL FAILURE PATIENTS THROUGH HEMODIALYSIS - Muhith, Abdul; Hidaayah, Nur; Anggreani, Rahayu; Hartadi, Hartadi (Nurse and Health: Jurnal Keperawatan, 2021)
Background: Disease Chronic kidney failure can result in positive and negative implications as Posttraumatic Growth (PTG) and problems mental - psychological include self-concept, and the quality of life of patients. Objectives: The research objective was to analyze the effect of spiritual based reiki therapy (prayer) on posttraumatic growth. Methods: The study design was Quasy-Experimental with pre-post test control group design and research conducted by a research assistant. The population was all chronic renal failure patients undergoing hemodialysis. Sample size 40, divided into 20 interventions and 20 controls. The sampling technique is purposive sampling. In the intervention group-based therapy reiki spiritual (prayer) for 45 - 75 minutes of 8-12 meetings (se whenever there are 3 sessions) performed 2 weeks. The control group was given action according to hospital standards. Test analysis Wilcoxon Signed Ranks Test and analysis uji depending Mann Whitney. Results: Results of analysis of test Wilcoxon Signed Ranks Test P no intervention group therapy reiki spiritually based (Prayer) no effect on posttraumatic growth p = 0.000. If the control group was given therapy according to hospital SOP, there was an effect on posttraumatic growth p = 0.025. And the results of the analysis using Mann Whitney found that Results Posttraumatic Growth in the intervention group of the therapy reiki spiritually based (Prayer) - In the group controls are enforcedi according to SOP hospital treatment, the results are no different, p = 0.000. Conclusion: Reiki therapy based spiritual (prayer) is very effective to decrease the Posttraumatic Growth, can improve quality of life and positive attitude in which respondents were willing to change his priorities and biases appreciate herself.